2004
DOI: 10.1103/physrevb.69.153202
|View full text |Cite
|
Sign up to set email alerts
|

Divacancy annealing in Si: Influence of hydrogen

Abstract: We have performed comparative studies of divacancy (V 2 ) annealing in hydrogenated and nonhydrogenated Si by deep level transient spectroscopy. It is shown that the nonhydrogenated samples demonstrate the formation of divacancy-oxygen (V 2 O) complex during annealing of V 2 , while the hydrogenated samples demonstrate annealing of V 2 without correlated growth of electrically active centers. No substantial formation of divacancy-hydrogen (V 2 H) complexes is observed in the hydrogenated samples. It is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…6) one observes a decrease of the well-known peaks E1 (VO+C i C s ), E2 (V 2 ( ¼ /À) ) and E4 (V 2 (À/0) ) and an increase of the signal E5 which is attributed to the hydrogen-related VOH complex. Similar measurements on oxygen-enriched and hydrogenated FZ samples had been performed by Monakov et al [34], revealing the same annealing behavior as shown in Fig. 6.…”
Section: Hydrogen In Siliconsupporting
confidence: 74%
“…6) one observes a decrease of the well-known peaks E1 (VO+C i C s ), E2 (V 2 ( ¼ /À) ) and E4 (V 2 (À/0) ) and an increase of the signal E5 which is attributed to the hydrogen-related VOH complex. Similar measurements on oxygen-enriched and hydrogenated FZ samples had been performed by Monakov et al [34], revealing the same annealing behavior as shown in Fig. 6.…”
Section: Hydrogen In Siliconsupporting
confidence: 74%
“…It appears, therefore, reasonable to assume that reaction (4) together with reaction (5) Figure 6 shows DLTS spectra of sample C annealed isochronally for 15 min from 175 • C to 400 • C in steps of 25 • C. Sample C was heat treated for 1 h at 450 • C after the HF and prior to the electron irradiation; in such pretreated samples, the generation of V OH * still exists, but is strongly suppressed. This is attributed to the fact that the 450 • C treatment distributes hydrogen more homogeneously and the locally high hydrogen concentration promoting reaction (1) in samples without preannealing diminishes. The amplitude decrease substantially, the V OH level emerges, and two new levels, labeled E2 and E3, appear, with energy positions of E c − 0.17 eV and about E c − 0.58 eV, respectively.…”
Section: Extended Annealing At 225 • Cmentioning
confidence: 84%
“…It is known, for instance, that the vacancy-oxygen (V O) center and the divacancy (V 2 ) center disappear at temperatures below 300 • C in the presence of hydrogen. 1 The V O center transforms into a V OH center, [2][3][4][5][6][7][8][9][10] while the annealing mechanism for the V 2 center is less documented, although there have been several suggestions that the hydrogen-mediated annealing may give rise to a divacancy-hydrogen (V 2 H) center. 2,9,11 Reported values for the migration energy of monatomic hydrogen in Si range from 0.48 eV (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to form a complex between VO and hydrogen, the reconstructed SiSi bond must be broken, which requires energy and slows down the reaction rate. This consideration is supported by the fact that the hydrogen-assisted annealing of VO takes place at higher temperatures than that of V 2 [27]. At these temperatures, the concentration of free atomic hydrogen increases because of release of trapped H from complexes and, possibly, also dissociation of H 2 , and the interactions VO+H→VOH and VOH+H→VOH 2 are promoted.…”
Section: Dlts Signal (Pf)mentioning
confidence: 90%
“…Thus, the reaction V 2 +H→V 2 H can be ruled out as a dominant one. Instead, it can be argued that the hydrogen dimer (H 2 ) is a common form of mobile hydrogen at 200-300 °C [27]. The V 2 center has two dangling bonds [12,13], and similar to the interaction of H 2 with the mono-vacancy [28], it may be energetically favorable to break up the H-H bond and saturate the two dangling Si bonds in V 2 .…”
Section: Dlts Signal (Pf)mentioning
confidence: 99%